2008
DOI: 10.1111/j.1365-2702.2008.02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of self‐reported fluid intake and its effects on body weight, symptoms, quality of life and physical capacity in patients with stable chronic heart failure

Abstract: Nurses involved in the care for patients with heart failure known how troublesome thirst can be and how difficult it can be to follow a restricted fluid intake. This study indicates that it is possible to reassess and recommend a less strict fluid intake in stabilised patients with chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 30 publications
1
49
0
3
Order By: Relevance
“…6,7,10 Intervention studies have shown that thirst intensity and thirst distress are increased in patients having a fluid restriction and decreased with a liberal fluid intake. 8,39,84,85 However, other studies have shown that there is no difference in thirst between patients having fluid restriction and those with a liberal fluid intake. 38,86,87 Finally, dehydration and the increased neurohormonal activation in HF may play an important role in causing thirst.…”
Section: Factors Related To Thirstmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7,10 Intervention studies have shown that thirst intensity and thirst distress are increased in patients having a fluid restriction and decreased with a liberal fluid intake. 8,39,84,85 However, other studies have shown that there is no difference in thirst between patients having fluid restriction and those with a liberal fluid intake. 38,86,87 Finally, dehydration and the increased neurohormonal activation in HF may play an important role in causing thirst.…”
Section: Factors Related To Thirstmentioning
confidence: 99%
“…Seven out of thirteen studies were randomized trials examining the effects of a fluid restriction. 8,38,39,[84][85][86][87] Three studies used qualitative methods to describe how it is to live with HF and to explore reasons and motivations for compliance with HF treatment. 6,7,10 A randomized controlled trial investigated effects of a drug for HF.…”
Section: Descriptions Of Thirstmentioning
confidence: 99%
See 3 more Smart Citations